Random telegraph signals originating from unrelaxed neutral oxygen vacancy centres in SiO2. Issue 20 (1st October 2015) - Nour, M.; Çelik‐Butler, Z.; Sonnet, A.; Hou, F.C.; Tang, S.
Abstract : Unrelaxed neutral oxygen deficiency centres (ODCs) (V 0 ODC II) in SiO2 have been identified as the cause of random telegraph signals (RTSs) in highly scaled n‐type metal–oxide–semiconductor field‐effect transistors. Variable temperature RTS measurements were performed to extract trap capture cross‐sections, capture activation energy, relaxation energy associated with the gate oxide defects, and the trap energy in the SiO2 bandgap to determine the trap species and type. The results indicate that the electron is captured by a neutral ODC that is transformed into a negatively charged vacancy (V − ). This is the first time V 0 ODC II centre is confirmed to be the source of electron switching through RTS measurements defining four different trap characteristics.